"Polvilho azedo": physical-chemical and microbiological aspects - Carvalho, Eliana Pinheiro de; Canhos, Vanderlei Perez; Ribeiro, Vilela Evódio; Carvalho, Helton Pinheiro de (Pesquisa Agropecuaria Brasileira, 1996)
This work was carried out at the DCA-ESAL, in Lavras, MG, Brazil, to study the processing conditions of the "polvilho azedo" (sour cassava starch) produced in the region of Macaia, MG. The pH and acidity values found in the samples taken directly from the sedimentation vat, showed that the fermentation already occurs there. The total counts of both aerobic and anaerobic microorganisms were not altered during fermentation of the cassava starch, showing that a shift of the bacterial microflora occurs due to a decrease in pH. Five hundred and ninety cultures were selected, of which 23 (3.9%) were lost ; consequently five hundred and sixty seven isolates were identified, of which 18 (3. 1 %) were gram-negative bacteria, 13 (2.2%) yeast; 46 (7.8%) bacteria of the genera Bacillus and Corynebacterium; 14 (2.4%) Staphylococcus and Micrococcus possible as a contaminant of the process, and 476 (80.6%) were identified as acid lactic bacteria, showing predominance of the later group. The identification of the isolates was done by the use of probability matrices, and a computer program. The water utilized in the process was also analyzed; the number of aerobic mesophylls in the water was 1.1 x 10³/ml; 9.5 x 10³/100 ml of total coliforms, and 2.5 x 10³/100 ml of fecal coliforms.